2016
DOI: 10.1021/acsami.5b11789
|View full text |Cite
|
Sign up to set email alerts
|

The Promising Nanocarrier for Doxorubicin and siRNA Co-delivery by PDMAEMA-based Amphiphilic Nanomicelles

Abstract: Synergistic effects of anticancer drug and siRNA have displayed superior advantages for cancer therapy. Herein, we deeply analyzed the feasibility that whether doxorubicin (DOX) and siRNA could be co-delivered by mPEG-PCL-graft-PDMAEMA (PECD) micelles, which mediated excellent DNA/siRNA delivery in vitro and in vivo reported in our previous work. DOX-loaded NPs (PECD-D) were developed by nanoprecipitation technology and exhibited high drug loading content (DLC, 9.5%). In vitro cytotoxicity study in MDA-MB-231 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 53 publications
0
55
0
Order By: Relevance
“…Also, siRNA target-specific gene silencing has been attempted for cancer therapy because cancers often overexpress a specific growth factor as well as rely on relevant receptor proteins for their growth and progression 11. Use of siRNAs to specifically silence genes for treating cancers or other diseases may have value 12-17, but successful implementation of nucleic acid drugs as new therapeutic tools largely depends on the appropriate delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Also, siRNA target-specific gene silencing has been attempted for cancer therapy because cancers often overexpress a specific growth factor as well as rely on relevant receptor proteins for their growth and progression 11. Use of siRNAs to specifically silence genes for treating cancers or other diseases may have value 12-17, but successful implementation of nucleic acid drugs as new therapeutic tools largely depends on the appropriate delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Dong and co-workers improved their PCL-g-PDMAEMA nanoparticles by coating PEG on the surface of PCL-g-PDMAEMA nanoparticles and obtained a new nanocarrier (PEG-b-(PCL-g-PDMAEMA)) for co-delivery of DOX and siRNA. [89] The PEG-b-(PCL-g-PDMAEMA) nanoparticles not only successfully co-delivered DOX and siRNA into MDA-MB-231 cells but also assisted in the endosome/lysosome escape process (Figure 7). In vivo experiments revealed that the PEG-b-(PCL-g-PDMAEMA) nanocarriers targeted and delivered both drug and gene to tumor tissues.…”
Section: Poly(dimethylaminoethyl Methacrylate) (Pdmaema)-based Drug/gmentioning
confidence: 99%
“…Multiple functions are integrated into a single carrier, including codelivery and pH‐responsive triggered release of drugs/small interfering RNA (siRNA), hepatic targeting, fluorescent tracking, as well as biocompatibility and safety. The cationic poly[(2‐dimethylamino)ethyl methacrylate] (PDMAEMA), a promising transporter for the nucleic acids delivery, was chosen to condense nucleic acids which are negatively charged to form stable complexes against enzymatic degradation with its amino groups . In addition, pH‐responsive PDMAEMA can transfect genes function when polymer swelling and endosomal escape due to the sponge effect is triggered in an acidic environment .…”
Section: Introductionmentioning
confidence: 99%